ANALISA WAKTU SEBAGAI FAKTOR PROGNOSIS PADA HEMATOMA SUBDURAL TRAUMATIK AKUT - Muhammad Zafrullah Arifin*, Firman Priguna Tjahyono*, Wienorman Gunawan* (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION HEAD TRAUMA IS THE MOST COMMONLY SEEN TRAUMA MECHANISM WHICH HAS THE HIGHEST MORTALITY RATE IN TRAFFIC ACCIDENT ONE OF THE IMPACT IS ACUTE TRAUMATIC SUBDURAL HEMATOMA ATSDH WHICH CAN REACH 4090 MANY FACTORS AFFECT THE OUTCOME DESPITE THE PRINCIPLE OF GOLDEN HOUR FOR SDH PATIENTS NO EVIDENCE EXISTS TO SUPPORT IT NOR DOES ANY SURGEON MANAGE TO DUPLICATE IT